Violation prooxidative-antioxidant stability at maize shoots at different level of accumulation of cadmium and nickel - Artyushenko, Tatiana; Gryshko, Vitalii (Acta Agraria Debreceniensis, 2010)
Joint influence of cadmium and nickel was investigated on the feature of their accumulation by the vegetative organs of 10-days’ old maize shoots. It was established that most intensively noted metals are taken in by the roots of shoots in the first 7 hours stressing influencing, while in leaves they appear only after a 7-hour long exposition. It was stated that the absorption process of the noted metals by a root system is carried by two-phase character. The indexes of inner-tissue contamination are calculated. Activating by the cadmium and nickel ions of lipid peroxidation as marker of the stressing influencing, and also was shown the proper increase of intensity of functioning of ascorbate peroxidase as the antioxidant enzyme protection of cell.